2014
DOI: 10.1016/j.shaw.2014.07.001
|View full text |Cite
|
Sign up to set email alerts
|

A 4-Year Follow-up Cohort Study of the Respiratory Functions in Toner-handling Workers

Abstract: BackgroundFocusing on the respiratory function for health effect indices, we conducted a cross-sectional study on workers who did and did not handle toner to compare the longitudinal changes.MethodsAmong 116 individuals who worked for a Japanese business equipment manufacturer and participated in the study, the analysis included 69 male workers who we were able to follow up for 4 years. We categorized the 40 workers engaged in toner-handling work as the exposed group and the 29 workers not engaged in these tas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 13 publications
3
13
0
Order By: Relevance
“…This suggested that one of the possible reasons the trend in the high prevalence of the subjective symptoms was inconsistent with the objective findings reported in other previous epidemiological studies was the influence of differences between the toner-handling group and the non-toner-handling group at baseline. In terms of the low respiratory toxicity of toner exposure, the results obtained by this cohort study on subjective respiratory symptoms and respiratory diseases showed the same direction as the results of long-term inhalation exposure studies in animals [42][43][44], and objective findings in the previous cohort studies [12][13][14][15].…”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…This suggested that one of the possible reasons the trend in the high prevalence of the subjective symptoms was inconsistent with the objective findings reported in other previous epidemiological studies was the influence of differences between the toner-handling group and the non-toner-handling group at baseline. In terms of the low respiratory toxicity of toner exposure, the results obtained by this cohort study on subjective respiratory symptoms and respiratory diseases showed the same direction as the results of long-term inhalation exposure studies in animals [42][43][44], and objective findings in the previous cohort studies [12][13][14][15].…”
Section: Discussionsupporting
confidence: 78%
“…Several cohort studies at toner manufacturing factories were conducted for similar purposes to our study [12][13][14][15]. All of these studies consistently reported a tendency for the prevalence of respiratory symptoms, such as cough, phlegm, wheezing, and shortness of breath, to be higher in the toner exposure group, although no significant differences have been found between the toner-handling group and non-toner-handling group.…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…Several epidemiological cohort studies aimed at investigating the health effects of toner particle exposure have been conducted at toner manufacturing plants [8][9][10][11]. No significant differences were reported between the toner-handling and non-toner-handling groups in terms of the development of new-onset lung fibrosis on follow-up chest X-ray examination.…”
Section: Discussionmentioning
confidence: 99%